Reaction kinetics of liquid phase air oxidation of p-cresol to p-hydroxybenzaldehyde - Kshirsagar, V. S.; Nadgeri, J. M.; Tayade, P. R.; Rode, C. V. (Applied Catalysis A-General, 2008)
The kinetics of liquid phase oxidation of p-cresol to p-hydroxybenzaldehyde has been investigated using insoluble cobalt oxide (CO3O4) catalyst at oxygen partial pressures in the range 0.1-1.5 MPa, reaction temperatures 333-393 K, p-cresol concentrations 0.49-1.53 kmol/m(3) and catalyst loadings 0.38-3.03 kg/m(3). The effects of oxygen partial pressure, reaction temperature, p-cresol concentration and catalyst loading on the initial rate of reaction have been studied. The initial rate varied linearly with catalyst loading up to 1.5 kg/m(3) beyond which it was independent of the catalyst loading while first-order dependence was observed with variation in oxygen partial pressure. A rate expression has been proposed considering Langmuir-Hinshelwood (LH) type mechanism, based on the initial rate data. A batch reactor model was also developed based on the kinetics studied and the concentration time profile predicted by the model was in good agreement with the experimental data. The activation energy for the liquid phase oxidation of p-cresol was found to be 39.6 kJ/mol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Co3O4; kinetics; p-cresol oxidation; XPS; XRD

Reply to the comments of vicente et al. on ``liquid phase oxidation of p-vanillyl alcohol over synthetic co-saponite catalyst'' applied clay science (2010), doi:10.1016/j.clay.2010.10.026 - Rode, Chandrashekhar V.; Garade, Ajit C.; Biradar, Narayan S.; Kshirsagar, V. S. (Applied Clay Science, 2011)